2014
DOI: 10.1111/pace.12527
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation of Focal Tachycardia Originating from the Right Atrial Free Wall during Upstream Phrenic Pacing to Avoid Phrenic Nerve Injury

Abstract: Catheter cryoablation during simultaneous upstream phrenic nerve pacing can lead to safe and effective elimination of focal atrial tachycardias originating from the RAFW close to the phrenic nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
1
0
3
Order By: Relevance
“…54 Early studies of FAT substrates showed poor outcomes using cryoablation 145,254 ; however, cryoablation may be a useful technique to avoid phrenic nerve injury when ablating FAT, or for a focus within a pulmonary vein. 259…”
Section: Cryoablation For Other Substratesmentioning
confidence: 99%
“…54 Early studies of FAT substrates showed poor outcomes using cryoablation 145,254 ; however, cryoablation may be a useful technique to avoid phrenic nerve injury when ablating FAT, or for a focus within a pulmonary vein. 259…”
Section: Cryoablation For Other Substratesmentioning
confidence: 99%
“…Aynı zamanda ilaçlara dirençli olup taşikardiyle ilişkili kardiyomiyopatiye yol açabilir. Böyle olgularda radyofrekans ablasyon veya kriyoablasyon yapılarak hastalık etkin ve güvenli şekilde bir tedavi edilebilir [21][22].…”
Section: Fokal Atriyal Taşikardiunclassified
“…Genellikle atriyum içine uygulanmış cerrahi girişim ve skar izleri reentry halkası için kaynak oluşturur. Ventrikül yanıtı uzun süre yüksek olduğu zaman hasta kalp yetersizliği riskiyle karşı karşıyadır [22]. Bu hastalarda yüksek atriyum hızı tromboembolik olaylar için risk oluşturmaktadır [1,3,5,24].…”
Section: Atriyal Flatterunclassified
See 1 more Smart Citation